The Use of Online Games for English Vocabulary Learning Media in Teacher Working Group: Some Advantages and Barriers - Reza Fadhilah, Muhammad; Andriyanti, Erna; Ramadana Putera, Agustian (International Journal of Education and Digital Learning (IJEDL), 2023)
This study aims to measure the extent of the Kahoot! Effectiveness in improving the professional competence of English teachers in terms of memorizing vocabulary. The study was conducted in the teacher working group (KKG or MGMP) by taking 30 English teachers at random. The system that will be carried out is by control and experiment class then compares the scores both of them. In addition, an in-depth exploration (mix method) was conducted by interviewing the teacher whether the Kahoot! may be used in the next forum. The results of the study showed that control group only could memorize 5,33 in average however experiment class got 8,6 in average so it means that there is 33% distinction between both of them. Then, this result is strengthened by calculation on Wilcoxon Signed Rank that showed that the sig value 0,002 is greater than 0.05 so it also means like aforementioned. Kahoot app! found it very helpful in memorizing vocabulary because of its flexibility that it can be accessed from anywhere (e-class) but there are still many senior teachers, who are technology savvy, cannot access kahoot! especially if it will be implemented in the KKG or MGMP of English teachers.